The disjuncture between confidence and cooperation: police contact amongst Polish migrants and established residents - Griffiths, Clare E. (European journal of criminology, 2018)
Trust and confidence in such criminal justice institutions as the police is considered crucial for the successful functioning of society and to allow for greater voluntary compliance and cooperation with institutions of control. There is a plethora of existing research, however, that shows the often strained relationships between the police and particular ethnic minority groups in the UK, Europe and the US, with such groups exhibiting a great deal of mistrust and lack of cooperation. This article aims to add to this body of literature by presenting the findings of a case study that used quantitative and qualitative methods to explore new Polish migrants’ and established local residents’ trust in and cooperation with the police following a period of mass migration in a small working-class town in the north-west of England. The key results show that, contrary to expectations, Polish migrants in fact have greater trust in the police than do the more established local residents in the area. Notwithstanding this high confidence, Polish migrants remain reluctant to contact the police. Adding greater complexity to Tyler’s ‘normative’ model of police contact (Tyler, 2006; Tyler and Fagan, 2008), the article presents the nuances of police relations with majority and minority groups in this working-class town.